y=-z-2

Simple and best practice solution for y=-z-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-z-2 equation:


Simplifying
y = -1z + -2

Reorder the terms:
y = -2 + -1z

Solving
y = -2 + -1z

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -2 + -1z

See similar equations:

| X+(X*.15)+(X*.20)=135 | | (2p-7)+6=11 | | 19x=226 | | 6y^2-10y=2y | | 10k-[4k+(-4+4k)]= | | (7+7i)-(-6-i)= | | 7x-11=-109 | | 59=-4s+8 | | 6+3(5x-6)=6-4(2x+1) | | 3b^0.5(2b^0.5+5b^3/2) | | -14+6x+7=2x+1+5x | | by=a+x | | yb=x+a | | -2(7x-1)+7=-14x+9 | | (4+9i)+(5-8i)= | | 3(4x-2)=-2(-6x+3) | | 10m^2=2m+3.14159 | | 8=-7x+4+2 | | 2(15d+45c)+5/6(12d+18c) | | 5*-1+4*5= | | 16=4x-5 | | -2k^2+72=0 | | y-12=0.666(x-6) | | -4x-1/2y=10 | | -7=4r | | 3c-2d=2 | | 3/4x-5-7/3x-1 | | 3b^1/2(2b^1/2+5b^3/2) | | 5(2x+8x)=0 | | 3x+5=12x-20 | | 3=2c-11 | | -d+-18=0 |

Equations solver categories